Faktor-Faktor yang Mempengaruhi dalam Menentukan Alokasi Dana Desa di Kecamatan - Robiah Adawiyah; Novita Eka Chandra (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2021)
Village funds are funds originating from the State Revenue and Expenditure Budget which are used for villages through the Regional Revenue and Expenditure Budget. Management of village funds must be transparent and orderly. To determine the allocation of village funds to the total population, the number of poor people, the area of ​​the region and the geographic poverty index. The method used to analyze these factors is multiple regression analysis. From the results of the analysis carried out, it is found that there is a significant influence between the total population, the number of poor people, the area and the geographic poverty index on the allocation of funds.